Técnicas de estudio en la enseñanza y aprendizaje de Lengua y Literatura, del quinto “B”, escuela “Alonso de Mercadillo”, periodo 2021-2022 - Durazno Yupangui, Guisella Dolores (2022)
The present research work: Study techniques in the teaching and learning of Language and Literature, has as general objective: To contribute to the improvement of the teaching and learning of Language and Literature of the fifth "B". The general objective is: To contribute to the improvement of teaching and learning of Language and Literature of the fifth "B" class of the school of Basic Education "Alonso de Mercadillo" city of Loja, through the implementation of different study techniques, guaranteeing the education of the student, which is highlighted by the following specific objectives: to support theoretically with the use of updated bibliography what is related to the study techniques, in the same way, to identify the advantages and disadvantages of the use of study techniques in the teaching and learning process of Language and Literature, finally, to propose alternative guidelines that help to solve the detected problem, in order to guarantee the use of study techniques, to improve the pedagogical process. The research was carried out with a descriptive quali-quantitative approach and under a non-experimental design. The following methods were used: scientific, observational, analytical, descriptive, statistical, synthetic and hermeneutic. The techniques and instruments used were: direct observation guide, questionnaire, interview and survey. A population of 38 students and 1 teacher was used with a non-probabilistic sampling. Among the main results, it was evidenced that the advantages of study techniques favor the pedagogical process of the students, raising their self-esteem for learning and understanding complex contents. Therefore, it was concluded that study techniques help to improve the student's academic performance, for which a didactic guide with activities on study techniques was developed with the sole purpose of contributing to the improvement of teaching and learning of the students. Key words: Study techniques, teaching and learning, Language and Literature, Types of apprenticeships